Post-Surgical Readmissions Among Women Undergoing Benign and Malignant Gynecologic Surgery [17]. (May 2016) - Cory, Lori A.; Latif, Nawar; Zhang, Xiaochen; Giuntoli, Robert; Morgan, Mark; Ko, Emily
Abstract : INTRODUCTION: To compare 30 day postoperative readmission rates and risk factors for readmission between women following benign and malignant gynecologic surgery. METHODS: We identified patients following benign and malignant gynecologic surgery in the National Surgical Quality Improvement Program database from 2006–2012. Data collected included surgical procedure, operative time, 30-day readmission, co-morbidities, pre-operative condition and serious postoperative morbidity. Standard statistical analyses were performed. RESULTS: 5% (654/13, 093) versus 1.75% (375/21, 331) of patients who underwent surgery for malignant and benign indications, respectively, were readmitted ( P <.001). Compared with benign patients, those with uterine cancer (OR 2.41, CI 2.07–2.81), ovarian cancer (OR 4.04, CI 3.38–4.81), cervical cancer (OR 2.41, CI 1.93–3) and other gynecologic malignancies (OR 3.10, CI 2.38–4.04) were more likely to be readmitted. Patients with gynecologic cancers were more likely to have comorbidities, worse preoperative condition and major complications ( P <.01). Independent factors for readmission for gynecologic cancer surgery included worse preoperative condition (OR 1.33, CI 1.14–1.54), complex surgery (OR 1.67, CI 1.23–2.25) and major complications (OR 2.71, CI 2.44–3.01), all P less than or equal to .001. In comparison, independent factors for readmission for benign surgery included presence of co-morbid conditions (OR 1.26, CI 1.09–1.46) and major complications (OR 9.26, CI 7.81–10.99), all P less than or equal to .002. CONCLUSION/IMPLICATIONS: Women with gynecologic malignancies are more likely to have a 30 day post-surgical readmission than their benign counterparts. Future studies are needed to identify the role of perioperative care in reducing post-surgical readmissions.